Food insecurity and its severity among adults receiving antiretroviral therapy in health facilities, northcentral Ethiopia: a multi-facility-based cross-sectional study - Boneya, Dube Jara; Ahmed, Ahmed Ali; Yalew, Alemayehu Worku (Frontiers in Public Health, 2024)
Background: Food insecurity plays a crucial role in predicting the spread of HIV due to the adverse effects of coping mechanisms adopted to mitigate it. However, there is a scarcity of context-specific evidence regarding food insecurity among HIV-infected adults. Therefore, this study aimed to assess the context-specific magnitude of food insecurity and associated factors among adults receiving antiretroviral therapy (ART) in health facilities in the North Shewa Zone, Ethiopia, ultimately contributing to the achievement of the 95-95-95 HIV treatment target in the local context. Methods: A multi-facility cross-sectional study was conducted among 865 HIV-infected adults receiving ART and have follow-up for their treatment. We included health facilities that provide ART, including four hospitals and six health centers. A log-binomial regression model was fitted to identify the association between food insecurity and independent variables. Adjusted prevalence ratios (APRs) with a 95% confidence interval were computed to measure the strength of the association. Results: In this study, 290(33.7%, 95% CI: 30.60, 36.91)) of HIV-infected adults studied had food insecurity during their treatment and follow-up, in which 152(52.41%, 95% CI: 46.64, 58.13) and 110 (37.93%, CI: 32.50, 43.68) of them were found to have severe and moderate forms of food insecurity, respectively. We found that being younger (APR=2.27, 95% CI: 1.12, 4.60), being female (APR=1.87, 95% CI: 1.03, 3.39), lacking formal education (APR=10.79, 95% CI: 14.74, 24.58), having lower educational status (APR=5.99, 95% CI: 2.65, 13.54), being daily laborer (APR=6.90, 95% CI: 2.28, 20.85), having low monthly income (APR=1.89, 95% CI: 1.11, 3.22), advanced WHO clinical stage(APR=2.34, 95% CI: 1.08, 5.10), and receiving ART for less than 4 years (AOR=2.28, 95% CI: 1.09, 4.74) were significantly associated with high proportion of food insecurity among HIV-infected adults. Conclusion: The magnitude of food insecurity among HIV-infected adults receiving antiretroviral therapy was high with an extremely high magnitude of severe food insecurity. The findings indicate the need for culture-specific nutritional interventions, focus on early ART stages, and strategies to improve education and income for HIV-infected adults, linking food insecurity and HIV in Ethiopia's national nutrition policy.